MODIFICATION POLISAKARIDA GALAKTOSA SULPHATE EXTRACTION EXPORT FROM GRACILARIA SP (ALGA MERAH) WITH ALKALI BOROHIDRIDA - Sri Atun (Jurnal Penelitian Saintek, 2001)
The   objective   of   the   study   is   to  modify   the   sulphate   galactanspolysaccharide  (gelatine) provided from  extraction of Gracilaria sp with borohydride  alkali and  its result  characterization.  The sample  of  this study   was   the   sulphate   galactans   polysaccharide   provided   from extraction of Graci/aria sp. The modified reaction using the Rees method used  NaBH4 and  NaOH  in  various  compositions.  The physical   and chemical characteristics of the modification reaction results were compared to the characteristics of the seaweed gelatine provided from the extraction before the treatment and agarosa p.a.  The result of this study indicates that the sulphate galactans polysaccharide can be modified by borohidrida alkali reagent in base condition at the composition variations of the seaweed gelatine:   NaBH4 : NaOH =  1:  0,5 : ] ; 1 : 1 : 2  and 1:   2  :   4  .The  characterization  showed  that  the  compound  of  the modification reaction result compared to the sulphate galactans polysaccharide   before  the  treatment  indicated  the  change  of  their physical   and   chemical   characteristics.   The   characteristics   of   the compound  resulted from   modification  reaction  of  sulphate  galactans polysaccharide  at the composition variations of the seaweed gelatine: NaBH4 : NaOH  = 1 :  1 : 2 and 1 : 2 : 4 were almost similar  to the characteristics of agarosa p. a.